On the behavior of electrokinetic streaming potential during protein filtration with fully and partially retentive nanopores - Sung, JH; Chun, MS; Choi, HJ (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2003)
An experimental investigation of the electrokinetic streaming potentials of both fully and partially retentive nanopores as compared with the filtration progress of dilute globular protein solution under different surface charge conditions was performed using hollow fibers. The streaming potential is generated by the electrokinetic flow effect within the electric double layer of the charged surface. Depending on the solution pH, both the protein and the pore wall can be either repulsive or attractive due to the long-range electrostatic interaction. The repulsive electrostatic interaction allows the protein particles to stay in a suspended state above the outer surface of hollow fibers instead of being deposited. The apparent streaming potential value at partially retentive pores is larger than that at fully retentive pores for the oppositely charged case; however, the opposite behavior is shown for the same-charged case. The axial-posit ion-dependent streaming potential was also observed in order to explore the development of a concentration polarization layer during the cross-flow filtration. The time evolution of the streaming potential during the filtration of protein particles is related to the filtrate flux, from which it can be found to provide useful real-time information on particle deposition onto the outer surfaces of hollow fibers. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: MICROFILTRATION MEMBRANES; ULTRAFILTRATION MEMBRANES; ZETA-POTENTIALS; FLOW